Anti-Inflammatory, Antiviral Veterinary Medicine with Immuno-Modulating Activity - Borisenko, N. N.; Bushuieva, I. V.; Parchenko, V. V.; Gubenko, I. Ya.; Mykhailiuk, Ye. O.; Riznyk, O. I.; Aleksieiev, O. G.; Gutyj, B. V.; Lysianska, H. P.; Kurinnyi, A. V.; Бушуєва, Інна Володимирівна; Парченко, Володимир Володимирович; et al. (My University, 2019)
The aim of this development is an estimation of the efficacy of veterinary medicine “Trifuzol 2,5% Solution for Injection” and comparative characteristics according to available domestic analogues. “Trifuzol 2,5% Solution for Injection” has an antioxidant, immuno-modulating, anti-inflammatory activity. The medicine increases resistance to the diseases with bacterial, viral, parasitic etiology. It is planned ahead to manufacture and sale the medicine on the internal and external pharmaceutical markets.
Keywords: Solution; trifuzol; efficacy; prevention; treatment